Improving Coverage and Signal Quality in Cellular Communications for Rural Areas - Achmad Ubaidullah (International Journal of Science, Engineering, and Information Technology, 2022)
Base Transceiver Station (BTS) is the center in a cellular telecommunications system. However, the coverage of the BTS signal to Mobile Station (MS) is limited to certain areas. The farther away from the BTS, the smaller the signal power received by the MS. The signal power received by MS in rural area is relatively low. This research is very important to help strengthen signal power from BTS to MS and increase coverage, especially in rural areas, so that rural communities can participate in these various online activities. Efforts to increase BTS signal coverage in this paper is the use of repeaters. The results of the study indicate that the coverage and signal quality can be improved and can assist rural communities in participating in the online learning system. Repeater application is proven to increase the Reference Signal Received Power (RSRP), Reference Signal Received Quality (RSRQ), Signal to Noise Ratio (SNR), the average Received Signal Strength Indicator (RSSI) and throughput. It also lowers the value of delay, jitter and packet loss.